Competitive abilities as a factor of market competitiveness for SME sector companies - Angelika Pańka (Nowoczesne Systemy Zarządzania, 2023)
The article presents the essence and interrelation of competitive abilities and market competitiveness of enterprises. The aim of the article was to assess the influence of the degree of development of particular components of competitive abilities on the market competitiveness of the surveyed enterprises of the SME sector, expressed by an increase in their market share compared with their main competitors. The implementation of the assumed objective was based on the results of a survey conducted with the CAPI technique among 1286 enterprises of the SME sector in the Kuyavian-Pomeranian Voivodeship. The results obtained in the empirical-analytical part indicate a significant influence of specific elements of the competitive abilities of enterprises in the SME sector, relating primarily to employee competence, research and development activities and possession of modern technologies on the increase in their market share compared with their main competitors. This leads the author to conclude that the market success of enterprises in the SME sector is determined by a clearly defined configuration of specific resources that form the desired competitive abilities.